Cost-effectiveness analysis of thermotherapy versus pentavalent antimonials for the treatment of cutaneous leishmaniasis (2023)
Objective: The treatment of cutaneous leishmaniasis is toxic, has contraindications, and a high cost. The objective of this study was to estimate the cost-effectiveness of thermotherapy versus pentavalent antimonials for the treatment of cutaneous leishmaniasis. Methods: Effectiveness was the proportion of healing and safety with the adverse effects; these parameters were estimated from a controlled clinical trial and a meta-analysis. A standard costing was conducted. Average and incremental cost-effectiveness ratios were estimated. The uncertainty regarding effectiveness, safety, and costs was determined through sensitivity analyses. Results: The total costs were $66,807 with Glucantime and $14,079 with thermotherapy. The therapeutic effectiveness rates were 64.2% for thermotherapy and 85.1% for Glucantime. The average cost-effectiveness ratios ranged between $721 and $1275 for Glucantime and between $187 and $390 for thermotherapy. Based on the meta-analysis, thermotherapy may be a dominant strategy. Conclusion: The excellent cost-effectiveness ratio of thermotherapy shows the relevance of its inclusion in guidelines for the treatment. © 2017 Chinese Cochrane Center, West China Hospital of Sichuan University and John Wiley & Sons Australia, Ltd